(untitled) (Journal of Foreign Language Studies, 2024)
This contrastive case study attempts to investigate the impacts of the EFL learners’ mother tongue on their use of English collocations. It involves one participant who has been learning English as a foreign language for 8 years. Error analysis was conducted to examine different types of collocational errors made due to the interference of Vietnamese. An English performance test including translation and writing tasks and an interview were used to collect qualitative data from the participant. The findings indicated that the learner’s mother tongue had great impacts on their use of English collocation and appeared to be the major cause of their collocational errors.